Handling Guest Complaints with the Identify, Listen, Empathize, Analyze, Deliver Solution Method at Intercontinental Bali Resort - Ariesa, Kadek Wahyu; Adi, Ida Ayu Sri Puspa; Indrayani, I Gusti Ayu Putu Wita (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The purpose of the study was to examine the application of the ILEAD method in handling guest complaints. The study was conducted using two methods, namely the interview method and the observation method. Interviews with staff in implementing ILEAD, direct and indirect observations of staff assessments in implementing ILEAD, and online travel agents assessing guest comments regarding the service provided by front office staff. Using qualitative analysis techniques. The results of the study showed that staff had implemented the ILEAD method correctly with the discovery of positive comments on online travel agents and assessments from Front Office Managers with a level of 80 percent of staff having implemented ILEAD. Although there were still some staff who still did not understand ILEAD correctly with negative comments found on online travel agents, direct observations, and there was a gap of 20 percent of staff understanding based on interviews with Front Office Managers. For some improvements to cover the gap, starting from more frequent or varied training, increasing cooperation between staff and superiors and evaluation of guest comments from online travel agents.